Marketing strategy to increase sales at PT. Jaya Beton Persada, Kandang Village, Bengkulu City - Ernitasari Ernitasari (Central Research Institute for Agriculture (CeRIA), 2022)
There are two issues studied in this thesis, namely, (1) How is the marketing strategy to increase sales at PT. Jaya Beton Persada, Kelurahan Kandang, Bengkulu City, (2) What is the marketing strategy to increase sales at PT. Jaya Beton Persada, Kelurahan Kandang, Bengkulu City, in terms of Islamic economics, the purpose of this research is to determine the marketing strategy to increase sales at PT. Jaya Beton Persada, Kandang Village, Bengkulu City. To find out the marketing strategy to increase sales at PT. Jaya Beton Persada, Kandang Village, Bengkulu City in terms of Islamic economics. To reveal the problem in depth and thoroughly, the researcher uses a qualitative descriptive method. From the results of this study it was found that (1) the marketing strategy to increase sales of PT. Jaya Beton Persada, Kandang Village, Bengkulu City uses a marketing mix. (2) Islamic economic review of marketing strategy to increase sales of PT. Jaya Beton Persada, Kelurahan Kandang, Bengkulu City, has implemented a marketing strategy in accordance with Islamic law.